TỔNG HỢP VÀ CẤU TRÚC CỦA MỘT SỐ N-ARYLIĐEN-2-HYĐROXY-5-IOĐOBENZOHYĐRAZIT - Tùng, Nguyễn Quang; Công, Nguyễn Tiến; Thanh Thảo, Châu Thị; Chi, Nguyễn Thị; Minh Nguyên, Nguyễn Thuỵ (Vietnam Journal of Chemistry, 2012)
Starting from salicylic acid, 2-hydroxy-5-iodobenzohydrazide and eight N-substituted hydrazides have been synthesized. The structure of the N-substituted hydrazides have been determined by IR and 1H-NMR spectra.